로봇 수술을 위한 CT-MRI-IR 피부 패치형 마커 정합 - Ryu, Jegyeong; Park, Chan Wook; Kim, Kyung Yeun; Kang, Joohyuk; Han, Amy Kyungwon; Lee, Won ryung; Lee, Deukhee (한국CDE학회 2025 동계학술대회 논문, 2025)
Robot-assisted surgery and surgical AR navigation are transformative technologies aimed at enhancing precision and safety in medical procedures. A critical component in these applications is stable marker registration, which ensures accurate transfer of imaging data, such as CT or MRI, to both robotic systems and human operators. In this study, we present a novel marker designed for medical environments, utilizing a patch marker. Marker attachment enabled precise registration, achieving sub-2 mm accuracy for both CT-MRI and CT-IR datasets. To evaluate the effectiveness of the registration, a robotic tumor-puncturing experiment was conducted, demonstrating successful reconstruction.